Terrace Car Parking System using PLC - Pattankar, Sangeeta; Mohan, Nikhil; Nimbalkar, Neeraj; Shinde, Vivek; Karande, Yogesh (International Journal of Computer Sciences and Engineering, 2025)
Now a days car parking is a big problem, most of we see there is no space or less space for parking the car. Most of the times car is parked on the road and because of this traffic problem occurs. On this problem we have a solution; the solution is “Terrace Car Parking System”. Most of times we see that roof or terrace space of our building is not in use so we can use it for car parking. For this we require building structure and car parking system which is suitable for parking the car. In this paper we discuss on car parking system.